The Influence of Teacher Competence, Strategies, and Technology Use on the Effectiveness of Learning in Islamic Education - Muaddyl Akhyar; Ilpi Zukdi; Salmi Wati; Kunalan Kuriaya; Ramil Abbasov (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: The Influence of Teacher Competence, Strategies, and Technology Use on the Effectiveness of Learning in Islamic EducationObjective: This study aims to examine the influence of teacher competence, teaching strategies, and technology use on the effectiveness of Islamic education at SMPN 4 Bukittinggi. Method: This study employed a correlational research design. Data were collected through questionnaires and analyzed using descriptive statistics. Results: The results showed that teacher competence, teaching strategies, and technology use collectively accounted for 58.6% of the variance in Islamic education effectiveness, while the remaining 41.4% was influenced by other variables not examined in this study. Conclusion: The findings reveal that teacher competence, teaching strategies, and the use of technology play a significant role in enhancing the effectiveness of Islamic education. Contribution: This study provides an empirical examination of the factors affecting the effectiveness of Islamic education, including teacher competence, learning strategies, and the use of technology. INDONESIAN: Pengaruh Kompetensi Guru, Strategi Pembelajaran, dan Penggunaan Teknologi terhadap Efektivitas Pembelajaran Pendidikan IslamTujuan: Penelitian ini bertujuan untuk menganalisis dan menggali lebih dalam mengenai pengaruh antara kompetensi guru, strategi pembelajaran, dan penggunaan teknologi terhadap efektivitas pembelajaran pendidikan Islam di SMPN 4 Bukittinggi. Metode: Desain penelitian menggunakan metode korelasional. Pengumpulan data menggunakan kuesioner. Analisis menggunakan statistik deskriptif. Hasil: Uji simultan menunjukkan bahwa ketiga variabel independen (pengaruh kompetensi guru, strategi pembelajaran, dan penggunaan teknologi) secara bersama-sama berpengaruh dengan signifikansi 58,6%, sedangkan 41,4% sisanya dipengaruhi oleh variabel lain yang tidak diteliti. Kesimpulan: Temuan penelitian mengungkap bahwa kompetensi guru, strategi pembelajaran, dan penggunaan teknologi memiliki peran penting dalam meningkatkan efektivitas pembelajaran pendidikan islam. Kontibusi: Penelitian ini berkontribusi sebagai kajian empiris mengenai faktor-faktor yang memengaruhi efektivitas pembelajaran pendidikan islam meliputi kompetensi guru, strategi pembelajaran, dan penggunaan teknologi.